TAHAPAN REHABILITAS TERHADAP PECANDU NARKOTIKA DAN GANGGUAN MENTAL PADA YAYASAN REHABILITAS DHIRA SUMAN TRITOHA - Shelly Agustin; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine and describe the stages of rehabilitation applied to narcotics addicts and individuals with mental disorders at the Dhira Suman Tritoha Rehabilitation Foundation. This research uses descriptive qualitative methods to obtain an in-depth understanding of the rehabilitation process carried out. Data was collected through direct observation techniques, in-depth interviews with related parties, and documentation analysis. It is hoped that the research results will provide a complete picture of rehabilitation strategies, the stages clients go through, and the effectiveness of the program in supporting the recovery of narcotics addicts and individuals with mental disorders. These findings can be a reference for other rehabilitation institutions in developing more effective and holistic programs.